2010
DOI: 10.1177/1941738109357298
|View full text |Cite
|
Sign up to set email alerts
|

Extra-articular Snapping Hip: A Literature Review

Abstract: Context:Snapping hip, or coxa saltans, is a vague term used to describe palpable or auditory snapping with hip movements. As increasing attention is paid to intra-articular hip pathologies such as acetabular labral tears, it is important to be able to identify and understand the extra-articular causes of snapping hip.Evidence Acquisition:The search terms snapping hip and coxa sultans were used in PubMed to locate suitable studies of any publication date (ending date, November 2008).Results:Extra-articular snap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(94 citation statements)
references
References 43 publications
(165 reference statements)
1
84
0
9
Order By: Relevance
“…It occurs in 5e10% of the general population. 1 Activities which require extreme hip movements usually precipitate painful snapping hip like in athletes, …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It occurs in 5e10% of the general population. 1 Activities which require extreme hip movements usually precipitate painful snapping hip like in athletes, …”
Section: Discussionmentioning
confidence: 99%
“…1 Diagnosing snapping hip is very challenging because of variety of causes which could be intraarticular or extraarticular. The intraarticular causes are synovial chondromatosis, labral tears, loose bodies, osteochondral fractures and hip instability.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported that SHS is more common in women than in men, and as early as adolescent years. A large case series showed a 62% prevalence of cases in women [6]. However, gender is not a risk factor statistically significant up today [6].…”
Section: Epidemiology and Pathogenesis Of Shsmentioning
confidence: 99%
“…They often report difficulty to get in and out of the car, standing up from a seated position and doing sports as running, dancing, and all physical activities that require an high hip range of motion 6 . Then, usually the patient is able to tell the examiner when the snap occurs and to reproduce it voluntary.…”
Section: Clinical Examination and Diagnosismentioning
confidence: 99%